Novel buckled graphenylene-like InN and its strain engineering effects - Laranjeira, José A.S. [UNESP] (2024)
This paper reveals the structural, electronic and mechanical properties of a novel inorganic graphenylene based on indium nitride (IGP-InN). The IGP-InN was characterized via density functional theory (DFT) simulations. The phonon dispersion shows the dynamic stability of IGP-InN, and molecular dynamics simulations confirm its thermal stability up to 700 K. Besides the electronic properties, the indirect band gap transition with energy (Egap) of 2.49 eV makes IGP-InN suitable for optoelectronic applications under UV–visible. Also, the Egap tunability with mechanical strain was analyzed, with a decrease of 1.19 eV in the Egap for tensile strains. The structural buckling plays an important role, with a transition to a planar structure for tensile strains. This work reveals a new class of 2D materials, buckled inorganic graphenylenes, and provides valuable insights into designing and optimizing graphenylene-like materials.